Cullin-associated and neddylation-dissociated 1 protein (CAND1) governs cardiac hypertrophy and heart failure partially through regulating calcineurin degradation. (August 2022) - Li, Xingda; Zhang, Yang; Zhao, Yue; Zhou, Yang; Han, Qilong; Yang, Ying; Zhang, Lingmin; Shi, Ling; Jin, Xuexin; Zhang, Ruixin; Gao, Haiyu; Xue, Genlong; et al.
Abstract: Pathological cardiac hypertrophy is a process characterized by significant disturbance of protein turnover. Cullin-associated and Neddylation-dissociated 1 (CAND1) acts as a coordinator to modulate substrate protein degradation by promoting the formation of specific cullin-based ubiquitin ligase 3 complex in response to substrate accumulation, which thereby facilitate the maintaining of normal protein homeostasis. Accumulation of calcineurin is critical in the pathogenesis of cardiac hypertrophy and heart failure. However, whether CAND1 titrates the degradation of hypertrophy related protein eg. calcineurin and regulates cardiac hypertrophy remains unknown. Therefore, we aim to explore the role of CAND1 in cardiac hypertrophy and heart failure and the underlying molecular mechanism. Here, we found that the protein level of CAND1 was increased in cardiac tissues from heart failure (HF) patients and TAC mice, whereas the mRNA level did not change. CAND1-KO+ /- aggravated TAC-induced cardiac hypertrophic phenotypes; in contrast, CAND1-Tg attenuated the maladaptive cardiac remodeling. At the molecular level, CAND1 overexpression downregulated, whereas CAND1-KO+ /- or knockdown upregulated calcineurin expression at both in vivo and in vitro conditions. Mechanistically, CAND1 overexpression favored the assembly of Cul1/atrogin1/calcineurin complex and rendered the ubiquitination and degradation of calcineurin. Notably, CAND1 deficiency-induced hypertrophic phenotypes were partially rescued by knockdown of calcineurin, and application of exogenous CAND1 prevented TAC-induced cardiac hypertrophy. Taken together, our findings demonstrate that CAND1 exerts a protective effect against cardiac hypertrophy and heart failure partially by inducing the degradation of calcineurin. Graphical Abstract: Schematic diagram depicting the proposed signaling mechanisms underlying the effects of CAND1 in the setting of cardiac hypertrophy. Cullin-associated and neddylation-dissociated 1 protein (CAND1) counteracts cardiac hypertrophy and heart failure partially through promoting the ubiquitination and degradation of calcineurin via enhancing assembly of Cul1/atrogin1/Calcineurin complex. ga1